Effects of Functional Discrimination Training on Initial Receptive Language in Individuals With Autism Spectrum Disorder. Issue 5 (September 2020) - Eldevik, Sigmund; Aarlie, Hege; Titlestad, Kristine B.; Kazemi, Ellie; Elsky, Greg
The success of behavior-analytic procedures to teach language to individuals with autism spectrum disorder (ASD) has been well established in the literature. Nevertheless, some individuals may not learn any receptive or expressive language following extensive teaching efforts. We examined the effects of two reinforcement contingencies, functional and arbitrary, on increasing the level of auditory–visual conditional discriminations in children with ASD with a history of having difficulty learning discriminations. We evaluated the effects of the reinforcement contingencies by comparing the number of trials needed to establish discriminations in an adapted alternating treatment design. We found that five out of eight participants showed more rapid acquisition and demonstrated discrimination between more items in the functional reinforcement condition. The remaining three participants did not exhibit any discrimination in either condition within the allotted 500 trials/20 days. These findings suggest that using functional reinforcement procedures may be a helpful alternative for individuals who do not learn discriminations through traditional procedures.